Genital Immune Cell Activation and Tenofovir Gel Efficacy: A Case-Control Study . (10th February 2022) - Liebenberg, Lenine J P; Passmore, Jo Ann S; Osman, Farzana; Jewanraj, Janine; Mtshali, Andile; Gerardo Garcia-Lerma, J; Heneine, Walid; Holder, Angela; Archary, Derseree; Ngcapu, Sinaye; Sivro, Aida; Mansoor, Leila E; et al.
Abstract: Genital inflammation (GI) undermines topical human immunodeficiency virus (HIV) pre-exposure prophylaxis (PrEP) efficacy through unknown mechanisms. Here, associations between activated endocervical CD4 + T-cell numbers and higher deoxyadenosine triphosphate (dATP) concentrations suggest that competition for intracellular metabolites within HIV target cells may reduce the efficacy of antiretroviral-based PrEP in women with GI.